Generative Mechanisms of the Adoption of Logistics Innovation: The Case of On‐site Shops in Construction Supply Chains. Issue 2 (20th May 2015) - Tanskanen, Kari; Holmström, Jan; Öhman, Mikael
<x xml:space="preserve">Abstract</x> Empirical studies of logistics innovations have focused on the innovation process, bypassing much the innovative artifact or solution design itself. Focusing on the artifact and solution design in a case study, we contribute to the emerging theory of logistics innovations through articulating the generative mechanisms of the adoption of logistics innovation, that is, the mechanisms through which the design of the solution enables its adoption. We study On‐site Shop, a rare example from the construction industry of a logistics innovation that has successfully migrated from a limited number of pilots to common practice. The case study is based on insights from participation in the design of the solution, and on 55 interviews conducted in a relationship triad consisting of three groups: (1) construction site users, (2) the solution designers, and (3) the suppliers. We propose that standard and efficient solution set‐up is the key enabler of logistics innovation's adoption at temporary construction sites. Communication and operating rules facilitate adoption in the triad, whereas internal and external integration further advance adoption by creating links between the innovative logistics solution and other activities. Finally, trilateral collaboration and congruent technological frames in the relationship triad sustain adoption over time.